1983
DOI: 10.1016/0014-5793(83)80304-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for the emergence of catecholamine‐sensitive adenylate cyclase and β‐adrenergic receptors in cultured hepatocytes

Abstract: Adult male rat hepatocytes, which normally respond poorly to β‐adrenergic agents, acquire such responsiveness during primary monolayer culture. We here show that the rise in catecholamine‐sensitive adenylate cyclase activity in hepatocytes in vitro is closely paralleled by an increase in the ability to bind the β‐adrenoceptor ligand [125I]cyanopindolol. The emergence of β‐adrenergic responsiveness did not require cell attachment or serum. Addition of dexamethasone, insulin, thyroxine or dihydortestosterone to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 27 publications
3
25
0
Order By: Relevance
“…We [24] and Nakamura et al [23] found that the increase in isoproterenol-sensitive adenylate cyclase activity as measured at 24 h required protein synthesis. To investigate the possibility that the rise might contain an early protein-synthesis-independent component (see also [30]) we examined the period from 0 h (plating) to 3 h in cycloheximide-treated vs control cells.…”
Section: Experimental Interferences With the Emergence Of Isoproterenmentioning
confidence: 59%
See 4 more Smart Citations
“…We [24] and Nakamura et al [23] found that the increase in isoproterenol-sensitive adenylate cyclase activity as measured at 24 h required protein synthesis. To investigate the possibility that the rise might contain an early protein-synthesis-independent component (see also [30]) we examined the period from 0 h (plating) to 3 h in cycloheximide-treated vs control cells.…”
Section: Experimental Interferences With the Emergence Of Isoproterenmentioning
confidence: 59%
“…In the period between about 5 h and 24 h of culturing, the increases in P-adrenoceptor binding and isoproterenol-sensitive adenylate cyclase showed close parallelism (Fig. 1, inset and also [24]). When the cells were kept in culture for more than 24 h, the receptor binding in most experiments continued to rise while the P-responsive These results indicate that the emergence of P-adrenoceptors is a very early event during primary culture of hepatocytes and that there is a relatively close relationship between this rise in receptor number and the increase in catecholaminesensitive adenylate cyclase activity.…”
Section: Temporal Relationship Between P-adrenoceptor Binding and Catmentioning
confidence: 69%
See 3 more Smart Citations